Osseous paleopathologies of Bonapartesaurus rionegrensis (Ornithopoda, Hadrosauridae) from Allen Formation (Upper Cretaceous) of Patagonia Argentina - Cruzado Caballero, Penélope (2021)
The paleopathological record provides relevant information about paleobiology and paleoecology of fossil organisms. Based on the information obtained from paleopathologies, it is possible to infer how these injuries affected inter- and intraspecific relationships among organisms, and their interaction with the environment. For instance, fractures and infections may affect their behavior, such as locomotion, strength, and stamina, leading in some cases to death. Here, we describe the injuries recorded in the hadrosaurid Bonapartesaurus rionegrensis and their possible implications in its paleobiology. Three pathologies have been identified, two in caudal vertebrae neural spines and the third in the left metatarsal II. The caudal vertebra MPCA-Pv SM2/17 presents a displaced fracture with an advanced stage of healing and probably related to a trauma. The caudal vertebra MPCA-Pv SM2/19 shows an almost fully healed fracture produced by an impact or stress event. Finally, in the metatarsal II there is an overgrowth of pathological bone that covers the shaft interpreted as probably a neoplasm (e.g., osteosarcoma). The suite of vertebral paleopathologies would have generated pain and discomfort during its daily activity.